Efektivitas Pemberian Pupuk Organik Terhadap Ketersediaan Hara P Pada Pertumbuhan Bibit Kelapa Sawit (Elaeisguineensis Jacq) di Tanah Ultisol - Saragih, Rista Fransiska; Tarigan, Raudha Anggraini (Universitas Medan Area, 2025)
Ultisol soil is a type of marginal soil that is widely found in Indonesia, covering about 25% of the total land area. Its characteristic characteristics such as the soil pH is very acidic ( 4.5), high aluminum saturation, as well as low macronutrient content (N, P, K), make this soil less fertile and not ideal for cultivating crops, including oil palm. One of the widely used approaches to improve the soil properties of ultisol is the application of organic fertilizers, especially manure. This study aims to examine the effectiveness of various types of manure (cows, chickens, goats) in increasing soil nutrient availability and oil palm seed growth. The method used is a systematic literature review with the PRISMA approach. The results of the study showed that chicken manure had the most significant influence on increasing pH, C-organic, P-available, and cation exchange capacity. Meanwhile, cow and goat manure also contributes to increasing the availability of N and K and improving soil structure. This study provides applicative recommendations for sustainable management of ultisol soils and supports optimal growth of oil palm seedlings.